KAJIAN INVESTASI, PENGELUARAN PEMERINTAH, TENAGA KERJA DAN KETERBUKAAN EKONOMI TERHADAP PERTUMBUHAN EKONOMI DI PROPINSI JAWA TENGAH - Kurnia Maharani; Sri Isnowati (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2014)
This study aims to explainE economic growth in Central Java Province. The variables that affect rate of economic growthis private investment,government investment,government spending, labor and economic openness. In this study, the dataused are secondary data published by the Central Bureau of Statistic and bank Indonesia. The data are annual data from1985 to 2010. The analysis tool used is regression Ordinary Least Square (OLS), using t test, F test, and classicalassumption. The result showed that in the partial private investment, government investment, government spending, laboris positive and significant impact on economic growth in Central Java. While economic openness variable is statisticallysignificant, negative effect on economic growth in Central Java. Taken together private investment, government investment,government spending, labor and economic openness affect economic growth in Central Java.Keywords: economic growth , private investment , government investment , government spending , employment , economicopenness .